The difficult patients in pain therapy: How to recognize and manage them - Giuseppe De Benedittis (Publiediting, 2005)
When physicians experience negative reactions to patients, they often perceive the patients as "difficult". Such patients make up 15% to 30% of primary care practice populations. They are those whom most physicians dread. The dependency of difficult patients heavily influences the doctor-patient relationship and the outcome of the treatment. These patients often present with physical symptoms that could not be medically explained. Pain is the most frequent complaint, though unrecognized psychopatological disorders are more prevalent among these patients. Conversely, difficult patients are rather common in chronic pain syndromes, particularly in back pain, failed back syndrome and atypical facial pain. Diagnosis can be achieved on phenomenological, psychopathological and psychodynamic grounds. The management of difficult patients can prove to be a tough task for both physicians and nurses, as they are time-consuming, draining the emotional resources of the therapist, and evoke feelings of aversion and frustration. Appropriate use of patient-doctor communication skills and an effort to improve relations with the patient through empathy, tolerance and non-judgemental listening are suggested as ways of transform a difficult encounter into a workable patient-doctor relationship.